PENGARUH STRATEGI POSITIONING MUSEUM TERHADAP KUNJUNGAN WISATA EDUKASI DI KOTA BANDUNG (SURVEY SEGMEN PASAR GENERASI Y) - Gaffar, Vanessa (THE Journal : Tourism and Hospitality Essentials Journal, 2011)
Bandung has many heritage buildings and museums that can be very attractive to tourists. Nowadays,Â many heritage buildings, especially museums are developed to cater the needs of students and youngsterÂ to improve their knowledge. Hence, visiting museum and many other heritage buildings becomeÂ activities in edu-tourism. Youngster and students are those in the segment of Genration Y that areÂ targeted by museum. The characteristics of Gen-Y is that they like something new and very update withÂ the newes technology. This Characteristic are really on the opposite sites of the appearance of museumÂ that contains history and heritage of the past. Hence, the museums as a heritage objects should developÂ good positioning strategy in attracting those segment. This research focus on the evaluation ofÂ positioning strategy that is implemented by some museums in Bandung city and its influence to thedecision making in visiting edu-tourism sites. The dimensions of positioning strategy consist of value,Â uniquenessm credibility, sustainability, and suitability. The result shows that the positioning strategyÂ has significant influence to the tourist decision making The most significant value is on theÂ â€œsustainabilityâ€ or the preference tendency of a museum to be exist in the long term.